2016
DOI: 10.1097/md.0000000000005693
|View full text |Cite
|
Sign up to set email alerts
|

Primary pulmonary choriocarcinoma in a male that was successfully diagnosed and treated

Abstract: Introduction:Primary pulmonary choriocarcinoma (PPC) is extremely rare, especially in males. It is characterized by a poor response to therapy and shortened survival times. Here, we report a successful diagnosis and modified treatment for PPC in a male and a review of the literature.Case presentation:This case report describes a 67-year-old male who was discovered to have a left pulmonary mass. The patient underwent a pulmonary lobectomy. Pathological examination showed a poorly biphasic differential tumor. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“… 3 Zhu et al’s literature review of primary pulmonary choriocarcinoma in males reflected only 29 cases reported by 2016. 5 In our study, the incidence of extragonadal choriocarcinoma in males estimated by SEER data was 0.022/100,000 people, and the incidence decreased from 1981.…”
Section: Discussionmentioning
confidence: 47%
“… 3 Zhu et al’s literature review of primary pulmonary choriocarcinoma in males reflected only 29 cases reported by 2016. 5 In our study, the incidence of extragonadal choriocarcinoma in males estimated by SEER data was 0.022/100,000 people, and the incidence decreased from 1981.…”
Section: Discussionmentioning
confidence: 47%
“…Cases of gestational, gonadal nongestational, or extragonadal primary choriocarcinomas in the liver, kidney, lung, or brain presenting with neurological impairment compatible with brain metastasis with intracranial hemorrhage have been reported . However, primary mediastinal choriocarcinoma is rare, and most often presents with symptoms such as coughing and chest pain .…”
Section: Discussionmentioning
confidence: 99%
“…Negative tests included blood cultures, HIV, auto‐immune disease (e.g., ANA, SMA) and antiphospholipid antibody syndrome panels. CBC showed hemoglobin of 13–14 g/dl (ref .4 g/dl) and hematocrit of 41% (ref 41.5–50.1%); aPTT was consistently shortened at 24 s (ref .1–33.8 s). Alanine transferase was slightly elevated at 35–55 U/l (ref 0‐30 U/l).…”
Section: Case Historymentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with clinical data in publications were aged from 4 months to 77 years. [123] The median age of the patients was 53.1 years. Most patients had symptoms such as pleuritic pain, hemoptysis, dyspnea, cough, or precocious puberty, whereas 1 case was asymptomatic, and the tumor was discovered by chest roentgenogram.…”
mentioning
confidence: 99%